Overview of the strategic session results: key aspects of the development of the guardianship and custody system in the Russian Federation until 2036 - Semya, G.V.; Kolesnikova, U.V. (Social Sciences and Childhood, 2025)
Context and relevance. The Plan of Main Events for Implementing the Decade of Childhood, as well as several assignments from the President of the Russian Federation, include the task of improving the structure and activities of guardianship and trusteeship bodies. Today, the system for protecting children's rights and interests is unable to fully and promptly respond to modern challenges. A strategic session serves as a tool that allows determining the development vector, evaluating current results, envisioning the future, and creating a clear action plan. Objective. During the course of the strategic session, it was aimed at forming an ideal vision within the professional community regarding medium-term and long-term perspectives (up to 2036), specifically concerning: organizations for orphans and children deprived of parental care, including their purpose, structure, categories of children and families, types of activity, etc.; guardianship and trusteeship authorities (competences, organizational structure, content of work, delegation of powers, personnel policy, professional development, interaction with organizations for orphaned children). The hypothesis suggests that developing a strategic approach to enhancing the system for safeguarding children's rights and interests will enable effective responses to both present and future challenges. Methods and materials. More than 250 leaders of organizations for orphans and guardianship and trusteeship bodies participated in the strategic session: 49 heads of guardianship and trusteeship authorities from 44 regions of Russia, 101 directors of institutions for orphans and children deprived of parental care from 58 regions. Methods used included focus group discussions, individual surveys, qualitative and quantitative analysis methods. Results. Vectors for refining the structure and activities of guardianship and trusteeship authorities and institutions for orphans were identified, along with measures to achieve set goals and conditions for their implementation, expected outcomes in the medium term. Conclusions. The conducted survey revealed a high level of readiness among specialists for changes in the system but also highlighted the need for further elaboration on issues related to power distribution and standardization of approaches. Контекст и актуальность. План основных мероприятий по реализации Десятилетия детства, ряд поручений Президента Российской Федерации содержат задачу совершенствования структуры и деятельности органов опеки и попечительства. Сегодня система защиты прав и интересов детей не в состоянии полноценно и своевременно ответить на современные вызовы. Инструментом, позволяющим определить вектор развития, оценить текущие результаты, представить будущее и создать четкий план действий, является стратегическая сессия. Цель. В ходе проведения стратегической сессии сформировать в профессиональном сообществе идеальное видение в среднесрочной и дальнесрочной (2036 год) перспективе: организаций для детей-сирот и детей, оставшихся без попечения родителей, включая назначение, структуру, категории детей и семей, виды деятельности и пр.; органов опеки и попечительства (полномочия, организационная структура, содержание работы, передача полномочий, кадровая политика, профессиональное развитие, взаимодействие с организациями для детей-сирот). Гипотеза заключается в том, что разработка стратегического подхода к развитию системы защиты прав и интересов детей позволит эффективно ответить на текущие и будущие вызовы. Методы и материалы. В стратегической сессии приняли участие более 250 руководителей организаций для детей-сирот и органов опеки и попечительства: 49 руководителей органов опеки и попечительства из 44 субъектов России, 101 руководитель организаций для детей-сирот и детей, оставшихся без попечения родителей, из 58 субъектов. Были использованы: метод фокус-групп, индивидуальный опрос, качественные и количественные методы анализа. Результаты. Определены векторы совершенствования структуры и деятельности ООиП и организаций для детей-сирот, меры достижения поставленных целей и условия их реализации, ожидаемые результаты в среднесрочной перспективе. Выводы. Проведенный опрос выявил высокую степень готовности специалистов к изменениям в системе, однако также показал необходимость дальнейшей проработки вопросов распределения полномочий и стандартизации подходов.